2011
DOI: 10.1017/s0007114511004831
|View full text |Cite
|
Sign up to set email alerts
|

Dietary treatment of cows' milk protein allergy in childhood: a commentary by the Committee on Nutrition of the French Society of Paediatrics

Abstract: The diagnosis of cows' milk protein allergy (CMPA) requires first the suspicion of diagnosis based on symptoms described in the medical history, and, second, the elimination of cows' milk proteins (CMP) from the infant's diet. Without such rigorous analysis, the elimination of CMP is unjustified, and sometimes harmful. The elimination diet should be strictly followed, at least until 9-12 months of age. If the child is not breast fed or the mother cannot or no longer wishes to breast feed, the first choice is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 93 publications
0
76
0
4
Order By: Relevance
“…Many of these formulae contain extensively hydrolyzed protein sources to decrease overall allergenicity (Dupont et al. 2012; Ludman et al. 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Many of these formulae contain extensively hydrolyzed protein sources to decrease overall allergenicity (Dupont et al. 2012; Ludman et al. 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Over 90% of the infants in our study had food allergy. Numerous studies have reported that AAF supports growth and alleviates diarrhea due to food allergies [7,8], and they are preferable to extensively hydrolyzed formulas for certain patients [7-10]. An additional incentive to use AAF is that allergic responses can occur with extensively hydrolyzed formulas because they may contain residual peptides that can elicit an allergic response in sensitized children [11-14].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases choosing a soya or an extensively hydrolysed formula (eHF), which the infant may also react to, may lead to a false negative diagnosis. Alternatively, choosing an amino acid formula (AAF) when not indicated increases the cost burden of managing CMA and may affect development of tolerance (albeit the data is very preliminary at this time) [19,20]. …”
Section: Reviewmentioning
confidence: 99%